Analisis Implementasi Teknologi Face Recognition Dalam Meningkatkan Kecepatan Dan Keamanan Verifikasi Identitas Penumpang Pada Proses Boarding Di Terminal 3 Bandar Udara Internasioal Soekarno-Hatta Tahun 2023 - Nugraha, Adi Tugas; Setiawan, Dodi Rahmat; Zulkifli, Zulkifli (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This research aims to identify and analyze the implementation of face recognition technology in improving the speed and security of passenger identity verification during the process at Terminal 3 of Soekarno-Hatta International Airport in 2023. This research method uses a qualitative approach. Data collection techniques using interviews: informants in this study are Avsec officers, gate officers of Soekarno-Hatta International Airport, passengers, and lecturers of the STIAMI Institute's Postgraduate Programs and Airport Operations (OBU) PPI Curug. Research results show that 1) To improve the functioning of the autogate at Soekarno-Hatta Airport, it is necessary to update the registration system, train and add officers, as well as improve communication and collaboration. Support for facial recognition technology is also important for efficiency and security. 2) The implementation of face recognition technologies at airports is aimed at accelerating and enhancing passenger identification security. Although effective in identity verification, obstacles such as failure to identify and a lack of information reduce the use of autogate. This technology has the potential to improve efficiency and security at airports. 3) To improve efficiency and comfort at the airport, the addition of autogates, the updating of the face recognition system, the improvement of the travel application, infrastructure upgrades, and socialization with passengers are required. It's also important to strengthen data security. This implementation is expected to make the airport process more efficient and comfortable.